2015
DOI: 10.1016/j.ajur.2015.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Impact of tertiary Gleason pattern 5 on prostate cancer aggressiveness: Lessons from a contemporary single institution radical prostatectomy series

Abstract: ObjectiveTo better evaluate tertiary Gleason pattern reporting and to evaluate the impact of tertiary Gleason pattern 5 (TP5) on prostate cancer pathological features and biochemical recurrence at our large single institution.MethodsWe retrospectively reviewed 1962 patients who underwent radical prostatectomy (RP) for prostate cancer; TP5 was reported in 159 cases (8.1%). Men with Gleason score (GS) 7 and GS 8 disease were divided into subgroups with and without TP5, and histopathological features were compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 26 publications
3
14
0
Order By: Relevance
“…Patients in GG2‐3 with tertiary Gleason 5 patterns had an increase in absolute risk of treatment failure of >20% at 6 years as compared to patients in the same group without tertiary Gleason pattern; the relative risk increase was 50% to 100%. In line with our findings, patients with Gleason 7 tumours in several other cohorts had a significantly worse prognosis if they had tertiary Gleason 5 pattern . In a retrospective study, 75 patients in GG2 and GG3 who had tertiary Gleason 5 pattern had similar biochemical recurrence rates to those in GG3 and GG4 without a tertiary pattern, respectively .…”
Section: Discussionsupporting
confidence: 89%
“…Patients in GG2‐3 with tertiary Gleason 5 patterns had an increase in absolute risk of treatment failure of >20% at 6 years as compared to patients in the same group without tertiary Gleason pattern; the relative risk increase was 50% to 100%. In line with our findings, patients with Gleason 7 tumours in several other cohorts had a significantly worse prognosis if they had tertiary Gleason 5 pattern . In a retrospective study, 75 patients in GG2 and GG3 who had tertiary Gleason 5 pattern had similar biochemical recurrence rates to those in GG3 and GG4 without a tertiary pattern, respectively .…”
Section: Discussionsupporting
confidence: 89%
“…In addition, most risk‐stratification schemas classify patients with Gleason scores 8–10 as high‐risk, without discrimination between Gleason score 8 vs 9–10. However, multiple studies have reported significantly worse outcomes in patients with Gleason pattern 5 . Sabolch et al assessed the impact of Gleason pattern 5 in patients treated with dose‐escalated radiation therapy and showed that patients with Gleason pattern 5 had significantly lower freedom from metastasis ( P < 0.002), cause‐specific survival ( P < 0.001), and overall survival ( P < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with Gleason score 7 cancer are deemed intermediate‐risk; however, this is a heterogeneous group with Gleason score 4+3=7 tumours portending a worse prognosis than Gleason 3+4=7 tumours . Similarly, patients with Gleason score 8–10 cancer are deemed high‐risk, but multiple studies have shown that the presence of Gleason pattern 5 disease is associated with worse clinical outcomes . The granularity of what was initially a system consisting of 25 possible combinations of primary and secondary patterns has been largely reduced to three risk groups.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] While most of so-called tertiary grading reported in the literature refers to a higher grade-typically pattern 5-the term has been used variably regarding extent, ranging from a more limited, minor, or less than 5% highergrade carcinoma component in initial publications 3,4 to a third most common pattern of any percentage. [6][7][8][9][10][11][12][13][14][15][16][17][18] The accepted method for reporting ''tertiary'' patterns also differs between needle biopsy and radical prostatectomy (RP). As codified by the International Society of Urologic Pathology (ISUP) 2005 and 2014 grading conferences, cases with 3 patterns on needle biopsy should be graded by using a ''first plus worst'' (most common þ next highest grade) strategy.…”
mentioning
confidence: 99%
“…21,22 For RP specimens bearing 3 grading patterns, since the pathologist may assess the entire tumor, the ''tertiary'' terminology has been recommended. 19 The latter recommendation is based on an array of studies 3,4,[6][7][8][9][10][11][12][13][14][15][16][17][18] showing that cancers with a tertiary higher-grade pattern (TP) are associated with increased stage and/or biochemical recurrence following RP when compared with their closest grading counterpart (eg, 4 þ 3 ¼ 7 with tertiary pattern 5 compared with 4 þ 3 ¼ 7). Paradoxically however, TPs are not routinely incorporated into predictive clinical models.…”
mentioning
confidence: 99%